Face recognition attendance system using Local Binary Pattern (LBP) - Shamsul J. Elias; Shahirah Mohamed Hatim; Nur Anisah Hassan; Lily Marlia Abd Latif; R. Badlishah Ahmad; Mohamad Yusof Darus; Ahmad Zambri Shahuddin (Institute of Advanced Engineering and Science, 2019)
Attendance is important for university students. However, generic way of taking attendance in universities may include various problems. Hence, a face recognition system for attendance taking is one way to combat the problem. This paper will present an automated system that will automatically saves student’s attendance into the database using face recognition method. The paper will elaborate on student attendance system, image processing, face detection and face recognition. The face detection part will be done by using viola-jones algorithm method while the face recognition part will be carried on by using local binary pattern (LBP) method. The system will ensure that the attendance taking process will be faster and more accurate.